2020
DOI: 10.2174/1570159x17666191127112339
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Release-regulating Metabotropic Glutamate Receptors: An Update

Abstract: Metabotropic glutamate (mGlu) receptors represent the largest family of glutamate receptors in mammals and act as fine tuners of the chemical transmission in central nervous system (CNS). In the last decade, results concerning the expression and the subcellular localization of mGlu receptors further clarified their role in physio-pathological conditions. Concomitantly, their pharmacological characterization largely improved thanks to the identification of new compounds (chemical ligands and antibodies recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Among glutamate receptors, the mGlu belonging to the group II function as inhibitory release-regulating autoreceptors in the CNS of mammals, including the spinal cord ( Gerber et al., 2000 ; Di Prisco et al., 2012 ; Di Prisco et al., 2016 ). These receptors preferentially locate nearby the site of transmitter exocytosis and are activated by glutamate exceeding the physiological level and diffusing beyond the synaptic active zone ( Olivero et al., 2019 ; Pittaluga, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among glutamate receptors, the mGlu belonging to the group II function as inhibitory release-regulating autoreceptors in the CNS of mammals, including the spinal cord ( Gerber et al., 2000 ; Di Prisco et al., 2012 ; Di Prisco et al., 2016 ). These receptors preferentially locate nearby the site of transmitter exocytosis and are activated by glutamate exceeding the physiological level and diffusing beyond the synaptic active zone ( Olivero et al., 2019 ; Pittaluga, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides genetic and epigenetic mechanisms of control of the mGlu2/3 receptors expression ( Chiechio et al., 2009 ), we recently demonstrated that their insertion in synaptosomal plasmamembranes as well as their releasing activity is controlled by mechanisms of “metamodulation” ( Olivero et al., 2019 ). The term “metamodulation” refers to the mechanism(s) of control of synaptic plasticity based on the functional crosstalk linking two receptors colocalized on the same nerve endings ( Sebastião and Ribeiro, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The term "metamodulation" [39,75,76] was first proposed to recapitulate the physical and functional integration of colocalized GPCRs [72][73][74][75], with particular emphasis to their impact on the efficiency of neurotransmitter release, but it is now extended also to the receptor-receptor interactions involving ionotropic receptors [77,78] or transporters [58].…”
Section: Somatostatin Receptors and Metamodulation In The Central Nervous Systemmentioning
confidence: 99%
“…The functional interaction is referred to as an "agonist-like interaction" when the final effect is higher than the sum of the receptor-induced events (i.e., the mGlu1-mGlu5 receptors [76] or the nACh-NMDA receptors interactions [58]), or, conversely, it is defined an "antagonist-like interaction" if the outcome is quantitatively lower (i.e., the mGlu2/3 and the 5-HT 2A receptors [79]).…”
Section: Somatostatin Receptors and Metamodulation In The Central Nervous Systemmentioning
confidence: 99%
“…Functional adaptations induced by antibodies recognizing the N-terminal of membrane receptors subunits also could be detected in isolated nerve endings (we refer to as synaptosomes). In particular, commercially available antibodies recognizing the NH2-sequence of receptor subunits affect the receptor-mediated control of transmitter exocytosis from these particles and can be used as pharmacological tools for the characterization of the subunit composition of metabotropic (22)(23)(24)(25) and ionotropic (26) receptors in synaptosomes isolated from different CNS regions ("the immunopharmacological approach") (23,26).…”
Section: Introductionmentioning
confidence: 99%